Towards a General Method for Using Cyclotron-Produced Ga68 to Manufacture Clinical and Research Ga68 Tracers - Ivan E. Wang; Kevin Cheng; Allen F. Brooks; Peter J. H. Scott; Benjamin L. Viglianti (Molecules)
The success of multiple nuclear medicine radiotherapeutics in treating cancer requires an increased supply of companion diagnostic imaging agents radiolabeled with gallium-68. Cyclotron production addresses the need for access to gallium-68 and has been validated for use with commercially produced sterile kits. For novel research tracers undergoing translational studies (IND or RDRC), developing and purchasing sterile kits is time- and cost-prohibitive. An on-cassette labeling method with terminal filtration allows non-sterile kits to be fabricated in-house, simplifying workflow and allowing multiple PET imaging agents to be evaluated using the same kit (i.e., parts, reagents, and timelist) with minimal variation. Using modified GE gallium chloride cassettes, four diverse clinically relevant tracers (DOTA-TOC, FAPI-04, pentixafor, and PSMA-11) were radiolabeled with gallium-68 to evaluate the approach using DOTA and HBED-CC chelator types. The tracers were all formulated according to established FDA-approved formulations and sterile-filtered using a PVDF membrane. The automated procedure is robust, tolerating DOTA and HBED-CC chelators, and can be used to screen numerous gallium-68 agents for rapid translation to clinical use.